BASE LINE DATA FOR INSECTICIDE RESISTANCE MONITORING IN BRINJAL SHOOT AND FRUIT BORER, LEUCINODES ORBONALIS GUENEE - KAUR, JAGDEEP; B. K. KANG; SINGH, BALWINDER (The Bioscan, 2014)
Studies were carried out to determine the baseline susceptibility of second instar larvae of brinjal shoot and fruit borer, Leucinodes orbonalis Guenee to novel insecticides and biopesticide viz. emamectin benzoate, indoxacarb, spinosad, chlorantraniliprole and delfin for the populations collected from three different locations viz. Amritsar, Malerkotla and Hoshiarpur of Punjab state. LC50 values obtained for different locations ranged between 0.061-1.6 ppm. Emamectin benzoate showed highest toxicity against L. orbonalis for Amritsar and Malerkotla populations with LC50 values 0.49 and 0.061 ppm respectively followed by chlorantaniliprole, indoxacarb, delfin and spinosad. However in Hoshiarpur population there was not any appreciable difference between the LC50 values of emamectin benzoate and indoxacarb. The toxicity ratios of emamectin benzoate for Amritsar, Malerkotla and Hoshiarpur populations were 3.26, 6.72 and 3.37 respectively. Baseline toxicity of these new insecticides will be helpful in understanding the level of resistance developed by this pest in future.